Enhancing the selectivity of Nafion membrane by incorporating a novel functional skeleton molecule to improve the performance of direct methanol fuel cells. Issue 1 (10th December 2019) - Li, Jialin; Bu, Fanzhe; Ru, Chunyu; Jiang, Hao; Duan, Yuting; Sun, Yinan; Pu, Xingtong; Shang, Lichao; Li, Xifang; Zhao, Chengji
Abstract : Conventional fillers have limitations on the modification of proton exchange membranes because of differences in the sizes and physicochemical properties of matrix molecules. Abstract : Conventional fillers have limitations on the modification of proton exchange membranes because of differences in the sizes and physicochemical properties of matrix molecules. Designing skeleton molecules is a vital way to address the limitations by enabling precise distribution in the matrix and inducing automatic nanoscale aggregation and separation of hydrophilic–hydrophobic phases. In this work, a novel SDF-PAEK polymer was synthesized with a rigid hydrophobic backbone, short high-density trifluoromethyl side chains and long flexible aliphatic pendant side chains as a skeleton molecule for the Nafion membrane. Due to the unique molecular interaction selectivity during the membrane formation process, SDF-PAEK automatically matches the Nafion molecular conformation by self-assembly. Combining an improved solution formulation and membrane-casting method, the degree of composition can therefore rise to 20%, which can effectively reduce the cost. Morphological studies show that there is a certain degree of bicontinuous phase microcrystalline domains, and the proton transport channels are highly concentrated. In contrast to the Nafion membrane, SDF-PAEK@Nafion-15% exhibits better performances with higher selectivity (9.73 × 10 4 S s cm −3 ) and single-cell maximum power density (PDmax –139 mW cm −2, at 80 °C), which demonstrates the feasibility of SDF-PAEK as a novel PEM skeleton molecule for fuel cell applications.